DISTRIBUTION OF SEAHORSES AND PIPEFISHES (TELEOSTEI, SYNGNATHIDAE) ALONG THE ITALIAN COAST - Ravisato, Miriam (Biologia Marina Mediterranea, 2024)
Human activities have significantly impacted coastal ecosystems, leading to habitat changes and degradation, resulting in biodiversity loss. Seahorses and pipefishes, with their unique biological and ecological characteristics, are highly susceptible to the effects of human activities and habitat alterations. A decade ago, the IUCN Red List of Threatened Species assessed all syngnathid species, most of which were labeled as 'Data Deficient,' underscoring the lack of information on their distribution, population trends, and threats. This study aimed to improve our understanding of the extinction risk facing syngnathids by conducting a review of published and unpublished sources on their distribution in the confined areas along the Italian coast. A limited number of syngnathid species were found at many sites, although pipefish showed a broader distribution, often coexisting with seahorses. Among the most frequently recorded species were S. abaster for pipefishes and H. hippocampus for seahorses. The study emphasizes the importance of identifying and studying previously unknown populations, especially in poorly researched regions, to enhance the conservation efforts for these vulnerable species.